Colocalization of endogenous TNF with a functional intracellular splice form of human TNF receptor type 2 - Schütze Stephan; Schneider-Brachert Wulf; Scherübl Christoph; Hehlgans Thomas; Männel Daniela N (BMC, 2005)
Abstract Background Tumor necrosis factor (TNF) is a pleiotropic cytokine involved in a broad spectrum of inflammatory and immune responses including proliferation, differentiation, and cell death. The biological effects of TNF are mediated via two cell surface TNF receptors: p55TNFR (TNFR1; CD120a) and p75TNFR (TNFR2; CD120b). Soluble forms of these two receptors consisting of the extracellular domains are proteolytically cleaved from the membrane and act as inhibitors. A novel p75TNFR isoform generated by the use of an additional transcriptional start site has been described and was termed hicp75TNFR. We focused on the characterization of this new isoform as this protein may be involved in chronic inflammatory processes. Methods Cell lines were retroviraly transduced with hp75TNFR isoforms. Subcellular localization and colocalization studies with TNF were performed using fluorescence microscopy including exhaustive photon reassignment software, flow cytometry, and receptosome isolation by magnetic means. Biochemical properties of the hicp75TNFR were determined by affinity chromatography, ELISA, and western blot techniques. Results We describe the localization and activation of a differentially spliced and mainly intracellularly expressed isoform of human p75TNFR, termed hicp75TNFR. Expression studies with hicp75TNFR cDNA in different cell types showed the resulting protein mostly retained in the trans-Golgi network and in endosomes and colocalizes with endogenous TNF. Surface expressed hicp75TNFR behaves like hp75TNFR demonstrating susceptibility for TACE-induced shedding and NFκB activation after TNF binding. Conclusion Our data demonstrate that intracellular hicp75TNFR is not accessible for exogenously provided TNF but colocalizes with endogenously produced TNF. These findings suggest a possible intracellular activation mechanism of hicp75TNFR by endogenous TNF. Subsequent NFκB activation might induce anti-apoptotic mechanisms to protect TNF-producing cells from cytotoxic effects of TNF. In addition, the intracellular and not TACE-accessible splice form of the hp75TNFR could serve as a pool of preformed, functional hp75TNFR.